Fostering Educational Equity Through Cross-Sector Collaboration: A Case Study of School-Company CSR Partnerships in Indonesia - Salniati Nasution; Muhammad Fadhli (Yayasan Sembilan Pemuda Indonesia, 2026)
This study focuses on examining the partnership pattern between educational institutions and the business sector in implementing Corporate Social Responsibility (CSR) programs in the field of education. The aspects analyzed include the initial circumstances leading to the establishment of the collaboration, the organizational governance model and practices of shared leadership, the mechanisms for implementing and controlling activities, strategies to strengthen trust and commitment among the stakeholders, and the implications of the collaboration for expanding learning opportunities and improving the quality of educational services. This research employs a qualitative approach with a case study design conducted at Faza Azkia Integrated Islamic Private Elementary School. The research participants include the school principal, educators involved in the planning, data collection, and implementation of educational CSR programs, as well as representatives from partner companies. Data were collected through in-depth interviews, document review, and analysis of CSR activity reports. The analysis process was carried out interactively through stages of data selection, information display, and conclusion drawing. The reliability of the findings was ensured through the application of both source and technique triangulation. The findings indicate that the collaboration was formed due to the socio-economic gaps among students, which were reinforced by corporate initiatives and the school’s formal mechanisms. The clarity of the institutional design and the collaborative leadership of the school principal play a crucial role in maintaining the effectiveness and sustainability of the program. Educational CSR collaboration has a positive impact on increasing access to education, student motivation, and academic achievement, although the equitable distribution of program benefits remains a major challenge in its implementation.